Genetic Diversity of Chinese Longsnout Catfish (Leiocassis longirostris) in Four Farmed Populations Based on 20 New Microsatellite DNA Markers - Lu Zhang; Chenyan Mou; Jian Zhou; Hua Ye; Zhen Wei; Hongyu Ke; Zhipeng Huang; Yuanliang Duan; Zhongmeng Zhao; Han Zhao; Huadong Li; Jun Du; et al. (Diversity, 2022)
Freshwater aquaculture has a long and vibrant tradition in China. The Chinese longsnout catfish (Leiocassis longirostris) is a popular economic freshwater fish native to China. Understanding the genetic structure of L. longirostris populations is important for ensuring the efficacy of management practices and the sustainability of future increases in production. In this study, we used Illumina sequencing technology to isolate 20 novel polymorphic microsatellites from the genome of L. longirostris. These microsatellites were used to analyze the genetic diversity of 240 L. longrostris individuals from four populations. Genetic diversity parameters (NA, HO, HE, I, PIC, and FST) of the four farmed L. longirostris populations were analyzed. The level of genetic differentiation among the four farmed L. longirostris populations (inferred by pairwise comparisons of FST values) was low, but the genetic diversity of these populations was high, indicating that they still provide useful sources of genetic variation that could aid in breeding efforts. The STRUCTURE and ADMIXTURE analyses indicated that admixture might be occurring in the four L. longirostris populations, especially between the MS and YB populations. Understanding the genetic diversity of farmed L. longirostris populations and inbreeding prevention could greatly aid in breeding and production. These newly isolated microsatellite markers and the high genetic diversity of L. longirostris populations in the main breeding areas have important implications for the breeding and stock management of L. longirostris.